Identification of Pops Organic Compounds in Sediment in the Cisangkuy Watershed Using GC-MS Analysis Method - Pharmawati, Kancitra; Pratomo, Helmi Hadi; Maria, Rizka (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
The Cisangkuy Watershed is a tributary of the Upper Citarum River located in the Bandung Basin, West Java. Based one previous research, one organic pollution in the Cisangkuy Watershed is the presence of POPs (Persistent Organic Pollutants) compounds. POPs are organic compounds that can last a very long time in the environment (persistent) and have toxic properties for organisms. This study aims to identify and analyse the organic content of POPs and sediments in the Cisangkuy Watershed, as well as to analyse the source of pollutants and categorise them based on the Stockholm Convention on Persistent Organic Pollutants. Identification of POPs compounds using gas chromatography-mass spectrometry (GC-MS) technique. Sediment sampling was conducted by grab sampling that involved 20 sampling points from upstream to downstream of the Cisangkuy Watershed (CS-1 to CS-20). Samples were collected from 9 sub-districts. The research location shows that the land activities at the sampling point include asphalt hot mix, pharmaceutical, textile, and manufacturing industries. The results showed the presence of 1,2-Benzenedicarboxylic acid, mono (2-ethylhexyl) ester, 4,8,12-Tetradecatrienenitrile, 5,9,13-trimethyl-, and 2-Hexyl-1-octanol compounds at sampling points from upstream to downstream. These compounds were derived from chemical industry effluents, fossil fuel combustion, and agricultural activities. The compounds are classified as ‘industrial waste’ and ‘industrial waste with antibiotic properties’ by the Stockholm Convention on Organic Waste Management.